Constitutional Promises and Ground Realities for Equal Access to Health Services in Nepal - Sharma, Tribhuwon; Aryal, Bhagwan; Giri, Surendra; Lamichhane, Shisir (Mangal Research Journal, 2025)
Nepal’s Constitution states that health is a right of citizens, and the National Health Policy 2019 guarantees that health access is universal and accessible to everyone. But it highlights serious inequalities between what was promised in the Constitution and the reality on the ground, especially for Dalits, women and indigenous communities. The systemic dissonance between policy-specific commitments and experiences have been addressed in this paper, with an emphasis on the issues of access to health care in Nepal. Through a rights-based analytical lens in 2023 a policy review of nation’s laws, official documents, research reports, and health surveys was carried out over the period 2000–2024. The results demonstrate that Nepal’s health system suffers from lasting geographic imbalances, chronic workforce shortages, infrastructural deficiencies, and entrenched social exclusion that hinder equitable access to health services. Specifically, 59% of rural households have health facilities within 30 minutes compared to 85.9% in urban settings, the health worker density is 0.67 per 1,000 population compared to the WHO benchmark of 2.3, and less than 1% of the facilities meet infection control standards. These conditions show a growing chasm between policy ideals and practice. The study suggests equitable allocation of resources, good local governance, community engagement, gender and caste awareness and institutional responsibility are the keys to solving the systemic gaps in health.